LIPID PROFILE AND LIPID PEROXIDATION IN BRONCHIAL ASTHMA - Parhi, Kamala Kanta; PK, Behera; Chatterjee, Gangadhar (International Journal of Clinical and Biomedical Research, 2018)
Background: Bronchial asthma, a chronic inflammatory condition, often triggered by allergy & oxidative stress, initiate lipid peroxidation& enhanced release of arachidonic acid from cell membrane. Regarding lipid profile in bronchial asthma patients many conflicting data were reported. Therefore we have conducted this study. Methodology: 50 clinically diagnosed bronchial asthma cases for lipid profile and lipid peroxidation levels were compared with 50 healthy controls. Results: In our study fasting serum HDL and LDL cholesterol level of cases respectively (52.32mg/dl ±3.58), (99.21mg/dl ±12.49) were found to be significantly higher when compared to controls (44.58mg/dl ±2.58), (103.44mg/dl ±10.55) (p-value <0.05). Mean plasma SOD level of cases (3.42 U/mL±0.74) was significantly lowered than controls (7.16 U/mL±0.52). Serum MDA level of cases (5.91nmol/L±0.88) was higher as compared to controls (3.00nmol/L±0.40). (p-value <0.001) Conclusion: Lipid profile in bronchial asthma patients (raised HDL& decreased LDL) provides some degree of protection to this patients against ischemic heart disease (IHD). But increased in lipid peroxidation as evidenced by decrease plasma SOD & raised serum MDA aggravate airway inflammation, smooth muscle contraction & increased vascular permeability Keywords: Asthma; Oxidative stress; Lipid peroxidation; Lipid profile.